An annotated catalogue of Elachistinae of the World (Lepidoptera: Gelechioidea: Elachistidae) - Kaila, Lauri (Zootaxa, 2019)
An annotated catalogue of world species of Elachistinae (Lepidoptera: Gelechioidea: Elachistidae) is presented. The classification follows recent phylogenetic studies. Genera and the species within each genus are listed in alphabetical order. All family, genus and species-group names of Elachistinae published before 28 August 2018 are treated. Sixty-six genus-group names are listed, 60 of which are nomenclaturally available. In the classification followed in this catalogue the species are placed in 10 genera. There are 1016 nomenclaturally available and 106 unavailable species-group names. Of these, 805 names are currently considered to represent valid species. For each species the following data are given: the reference to the original publication and the page; type locality; deposition of the name-bearing types; in the genus Elachista, the taxonomic rank with the subgenus and the informal species group when applicable; distribution; larval host plants; references to essential illustrations, and remarks, when needed. Synonyms are listed under valid names; distribution with geographic area and country records, for Australia, Canada and U.S.A. territories, provinces and states are given; Russia is divided into subregions. Larval host plant records are listed with notes regarding uncertain records. When possible, original references that are considered trustworthy in later literature are given, as well as relevant literature references for illustrations for each species. Synonymies, incorrect subsequent spellings and misspellings are listed under each species with full reference. Alphabetical lists are given for subfamily and infra-generic groupings of species of the genus Elachista, to summarize the placement of each species in its subgenus and species group within the subgenera. 110 valid and one unavailable species-group names originally described to genera currently considered elachistines, but later removed, are listed. When known, their current identity is given. The following taxonomic changes are made: Elachista amseli (Parenti, 1981), a secondary junior homonym of E. amseli Rebel, 1933, is replaced with E. parentii nom. nov.; Hemiprosopa asiatica Sinev, 1998 = Elachista asiatica (Sinev, 1998) stat. nov., comb. nov.; E. bipunctella (Sinev & Sruoga, 1995), a junior secondary homonym of E. bipunctella Treitschke, 1833, is replaced as E. ochropunctosa Kaila, nom. nov.; Elachista cerusella f. juncta Dufrane, 1957 is raised as species-rank name Elachista juncta Dufrane, 1957 stat. nov., a synonym of E. maculicerusella Bruand; Svenssonia corsicana Tautel & Nel, 2010 is transferred to Elachista (Aphelosetia), comb. n.; E. cupreella Blanchard, 1852 is transferred to Perittia, comb. nov.; E. flammeaepennella Costa, 1836 is raised as valid species, stat. rev.; Illantis Meyrick, 1921 is considered a junior subjective synonym of Elachista, syn. nov.; I. picroleuca Meyrick, 1921 is transferred to Elachista, comb. nov.; E. kosteri Traugott-Olsen, 1995 = E. differens Parenti, 1978, syn. nov.; E. oritropha Bradley, 1965 = E. iriphaea (Meyrick, 1932), syn. nov.; Paraperittia Rebel, 1916 = Phaulernis Meyrick, 1895 (Epermeniidae) syn. nov.; P. uniformella Rebel, 1916 = Phaulernis dentella (Zeller, 1839), syn. nov.; and E. zernyi Hartig, 1941 = E. stelviella Amsel, 1932, syn. nov. A lectotype is designated for Paraperittia uniformella Rebel. Elachista macquartella Duponchel, 1840 is considered a nomen oblitum, stat. nov.